The Program of Teachers’ Accompaniment on the Learning of Science at Madrasah Ibtidaiyah - Ade Yeti Nuryantini; Rima Wiana; Ea Cahya Septia Mahen (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract The program of USAID PRIORITAS has a follow-up activity in form of accompaniment program. The accompaniment is committed to ensure that the teachers apply the training results. One of the accompaniments is carried out at MI Al Misbah Cipadung Bandung to apply module 3 related to skills of science. Focus of the accompaniment is to observe the feasibility of accompaniment activities, examine students’ skills in doing an experiment and making an experimental report. Data are acquired through observation and assessment rubric. The results of observation show that the teachers carry out six observed aspects, (setting of students’ seats, teachers’ role as facilitator, serving individual difference, paying attention to gender, the learning using the scientific approach, and students’ works), while the aspect of assessment of authenticity and literacy is not carried out. The average of students’ skills in carrying out and writing down the experiment belongs to good category.Abstrak Program USAID PRIORITAS memiliki aktifitas tindak lanjut berhubungan dengan pendampingan guru. Program pendampingan dibuat untuk memastikan para guru mengaplikasikan hasil pelatihan. Salah satu bentuk pendampingan dilaksanakan di MI Al Misbah Cipadung Bandung untuk mengaplikasikan modul 3 yang berhubungan dengan kemampuan sains. Focus dari pendampingan adalah mengobservasi kemungkinan dilaksanakan kegiatan-kegiatan pendampingan, menguji kemampuan siswa dalam melakukan eksperimen dan menuliskan hasilnya. Data didapatkan melalui observasi dan penilaian berdasar rubric. Hasil observasi menunjukkan bahwa para guru memiliki enam aspek, (mengatur tempat duduk siswa, guru sebagai fasilitator, memahami perbedaan individu, memperhatikan perbedaan gender secara merata, pembelajaran menggunakan pendekatan saintifik, dan kerja siswa), di sisi lain otentisitas penilaian dan kemampuan literasi tidak digunakan. Rata-rata kemampuan para siswa dalam melakukan dan menuliskan hasil eksperimen berada pada tahapan baik.How to Cite : Nuryantini, A., Y. Wiana, R. Septia, E., C., S. (2016). The Program of Teachers’ Accompaniment on the Learning of Science at Madrasah Ibtidaiyah. TARBIYA: Journal Of Education In Muslim Society, 3(2), 140-147. doi:10.15408/tjems.v3i2.4672. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.4672